Resolving the Constraints in Accessing Microcredit: The Neglected Views of the Smallholder Farmers - Jumpah, Emmanuel Tetteh; Adams, Abdulai (International Journal of Social and Administrative Sciences, 2020)
Access to financial resources by smallholder farmers remain a daunting challenge in spite of increasing numbers of Microfinance Institutions (MFIs) in Ghana. This paper contributes to the debate in addressing gaps created by an ever increasing numbers of MFIs yet the declining number of small businesses, particularly smallholder farmers having access to credit. Using data from 104 smallholder farmer microcredit borrowers of Ada East in the Greater Accra Region, the paper analysed the constraints preventing borrowers from accessing microcredit. Random sampling was used to obtain information from farmers using semi structured questionnaire. The Kendell Coefficient of concordance was used to analyse the result to establish the level of agreement among farmers perception about the constraints associated with application and granting of loans. High interest rate (1.76 mean rank) was found to be the most critical constraint. Other constraints in accessing microcredit were credit inadequacy, short repayment duration and farmer based organizations (FBOs) membership requirements. It is recommended that MFIs should put in place mechanism to lower operational costs in order to reduce the cost of borrowing. Finally, simplifying loan application procedures and reducing bureaucracies to reduce delays in loan disbursement will minimize the constraints in access to microcredit.